Rekombinantni človeški proteini - nov nabor učinkovin za zdravljenje luskavice - Kristl, Jernej (Medicinski razgledi, 2005)
Psoriasis is a chronic, inflammatory disease, which is estimated to affect 2,5% of the worldćs population. Clinically it is characterized by thickened, silvery white, scaly plaques, that can produce considerable discomfort and pain in patients. For the treatment of psoriasis are currently mainly used corticosteroids, vitamin D analogs, ultraviolet A radiation and retinoids, allof which are nonspecific and unable to block the outbreak of disease. Advances in recombinant DNA technology and increased understanding of the pathophysiology of psoriasis have led to the development of numerous immunomodulatory drugs, which specifically inhibit the occurrence of disease. Novel agents have direct effect on T cell, T cell activation, T cell migration, and expression of inflammatory mediators. However, they can still not assure total remission, but offer enhanced efficacy and improved safety. We have to take into consideration that treatment of psoriasis is usually longterm, meaning that adverse effects of a drug represent a limiting factor for using that drug. In this article, known facts on psoriasis are presented, along with the review of therapies with stress on new immunomodulatory agents.
Keywords: kožne bolezni; luskavica; therapy; zdravljenje; farmakologija; rekombiantni proteini; monoklonalna protitelesa; citokini